Diversity and Conflict - Cemal Eren Arbatli; Quamrul H. Ashraf; Oded Galor; Marc P. B. Klemp (Center for Economic Studies and ifo Institute (CESifo), 2018)
This research advances the hypothesis and establishes empirically that interpersonal population diversity has contributed significantly to the emergence, prevalence, recurrence, and severity of intrasocietal conflicts. Exploiting an exogenous source of variations in population diversity across nations and ethnic groups, it demonstrates that population diversity, as determined predominantly during the exodus of humans from Africa tens of thousands of years ago, has contributed significantly to the risk and intensity of historical and contemporary internal conflicts, accounting for the confounding effects of geographical, institutional, and cultural characteristics, as well as for the level of economic development. These findings arguably reflect the adverse effect of population diversity on interpersonal trust, its contribution to divergence in preferences for public goods and redistributive policies, and its impact on the degree of fractionalization and polarization across ethnic, linguistic, and religious groups.
Keywords: D74; N30; N40; O11; O43; Z13; 330; social conflict; population diversity; ethnic fractionalization; ethnic polarization; interpersonal trust; political preferences